Nanoscale membrane electrolyte array for solid oxide fuel cells - Su, Pei-Chen. (2013)
This paper presents a fabrication method for a low temperature micro-solid oxide fuel cell (μ-SOFC), featuring a large number of free-standing nano thin film electrolyte membranes. The μ-SOFC was fabricated by simple silicon-based MEMS processes to create a membrane array structure that renders high surface area density and mechanically stable support for yttria-stablized zirconia (YSZ) with only 70 nm in thickness. A total number of 765 to 6885 circular YSZ electrolyte membranes with a diameter of 50 μm were enclosed within 2 mm to 6 mm square arrays. The active membrane area density on a silicon wafer surface was increased up to 20 times higher than that of previously reported structures. A 2 mm μ-SOFC array was tested at 350, 400, and 450 °C, and maximum power outputs of 1.78 mW, 2.43 mW, and 2.98 mW were obtained, respectively. Total power output of the high performance micro-SOFCs was increased from microwatts up to the milliwatt scale, and can be easily scaled up further for higher power output by this method.